Efektivitas Model Pembelajaran Snowball Throwing terhadap Hasil Belajar Siswa pada Mata Pelajaran Aqidah Akhlak - Mashuri, Imam; Fauzi, Anis; Mufidah, Lailia (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Education plays a critical role in enhancing the quality of human resources by improving intellectual and character development. In the context of religious education, the teaching of Aqidah Akhlak is vital for shaping students' moral character in accordance with Islamic values. However, traditional teaching methods, such as lectures, often lead to passive learning and reduced student engagement. This research investigates the effectiveness of the Snowball Throwing learning model, a more interactive approach, in enhancing the learning outcomes of students in Aqidah Akhlak at MTs Roudlotul Muta’allimin Simbar Cluring Banyuwangi. Using a Quasi-Experimental Design with a Nonequivalent Control Group, this study involved 44 students selected through cluster sampling, divided into an experimental group (class VIII A) and a control group (class VIII B). Data were collected using observations, interviews, tests, and documentation, and analyzed using normality tests, homogeneity tests, and T-tests (paired sample t-test). The results showed a significant improvement in the learning outcomes of the experimental group, with a t-count of -22.363 and a significance value of 0.000, indicating that the Snowball Throwing model is more effective than traditional methods. The correlation coefficient of 0.845 further confirms the high effectiveness of this model. Thus, the Snowball Throwing learning model can significantly enhance students' engagement and learning outcomes in Aqidah Akhlak.